(untitled) (Pakistan Journal of Science, 2020)
FMD serotype “O” with subtype PAN Asia-II, serotype “A” with subtype Tur-06 and serotype “Asia-1” with subtype Sindh-08 were adapted on the LFBK cell line and subsequently on BHK-21. After inactivation these subtypes were introduced for the development of oil based trivalent vaccine against FMD. The study was conducted on the experimental animals (cow calves) at Livestock Production Research Institute (LPRI), Okara. Twenty one unvaccinated cattle calves of age group 4-6 month were used in the study, 16 were injected with experimentally prepared oil based FMD vaccine at the dose rate of 2cc per cow calf at day 0 and 28 post priming while five cattle calves were kept as control. The FMD oil based vaccine containing subtypes PAN ASIA-II, TUR-06 and SINDH-08 showed satisfactory immune response on ELISA and Serum Neutralization Test (SNT) at day 28 post priming and day 28 post booster. The study aimed to strengthen the national control strategy against FMD by the incorporation of prevalent field strains of FMD virus for the vaccine development.